2017
DOI: 10.1128/genomea.01280-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Novel Nonnodulating Rhizobium Species Isolated from Agave americana L. Rhizosphere

Abstract: We report here the complete genome sequence of Rhizobium sp. strain ACO-34A, isolated from Agave americana L. rhizosphere. No common nod genes were found, but there were nif genes for nitrogen fixing. A low average nucleotide identity to reported species supports its designation as a novel Rhizobium species that has a complete ribosomal operon in a plasmid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…In the endophytic microbiome of Musa spp., we found predicted phage or prophage sequences that were diverged from those of reference phage, suggesting that these phages may be unique to bacterial endophytes or pathogens of banana. Among the abundant and widely shared phages identified in these Musa samples, several resembled Rhizobium phage RR1-A and RR1-B, which are temperate phages first characterized from deep subseafloor sediments (Engelhardt et al, 2013), but also found associated with the rhizosphere of plants, such as Agave americana (Ruíz-Valdiviezo et al, 2017). Phylogenetic comparisons suggested that this phage may be related to phage infecting R. skierniewicense, an endophytic tumorcausing rhizobium (Pulawska et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…In the endophytic microbiome of Musa spp., we found predicted phage or prophage sequences that were diverged from those of reference phage, suggesting that these phages may be unique to bacterial endophytes or pathogens of banana. Among the abundant and widely shared phages identified in these Musa samples, several resembled Rhizobium phage RR1-A and RR1-B, which are temperate phages first characterized from deep subseafloor sediments (Engelhardt et al, 2013), but also found associated with the rhizosphere of plants, such as Agave americana (Ruíz-Valdiviezo et al, 2017). Phylogenetic comparisons suggested that this phage may be related to phage infecting R. skierniewicense, an endophytic tumorcausing rhizobium (Pulawska et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Además, se ha demostrado que R. etli inhibe la proliferación de patógenos en plantas de papa y maíz (Reiter et al, 2002;Rosenblueth y Martínez-Romero, 2004). Obtuvimos una nueva especie no nodulante de Rhizobium de las raíces de agaves en Chiapas con propiedades de promoción del crecimiento vegetal (Ruiz-Valdiviezo et al, 2017).…”
Section: Rizobios En Plantas No Leguminosas De Méxicounclassified